HUBUNGAN ANTARA LINGKUNGAN KERJA DAN MOTIVASI DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) GURU DI SMA NEGERI SE JAKARTA TIMUR - Supadi Supadi; Winda Dewi Listyasari (Program Studi Manajemen Pendidikan, 2018)
Abstract This study aims to determine whether there is a relationship between work environment and motivation with organizational citizenship behavior of public sma teachers in east jakarta. This research is a quantitative research with 3 variables in it are: (X1) work environment as independent variable, (X2) Motivation as independent variable and (Y) organizational citizenship behavior as dependent variable.The research method used is survey method with correlational study result. The population in this study is the public smp teachers in kecataman pulogadung. Samples were taken using Simple Random sampling technique or simple random sampling. Based on the technique, the sample size used in this research is 96 employees. Data collection for work environment variable (X1), motivation (X2) and organizational citizenship behavior (Y) using questionnaire The result of the research shows that: (1) there is a positive relationship between work environment with organizational citizenship behaviorI (OCB); (2) there is positive relationship between motivation with organizational citizenship behavior (OCB); (3) there is positive relation between work environment and motivation -together with organizational citizenship behavior (OCB)